2017
DOI: 10.1590/s0100-736x2017000200006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Anaplasma platys, Ehrlichia canis and Babesia vogeli in stray dogs in Paraná, Brazil

Abstract: Hemoparasitic infections are tick-borne diseases, which affect animals and humans. Considering the importance of canine hemoparasitic infections in veterinary clinics, this study aimed to determine the occurrence of Anaplasma platys, Ehrlichia canis and Babesia vogeli in blood samples from 182 dogs not domiciled in the city of Pato Branco, southwestern region of Paraná State, Brazil, using polymerase chain reaction (PCR). The prevalence of A. platys and B. vogeli was 32.9% and 10.9% respectively, and A. platys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 49 publications
2
17
0
6
Order By: Relevance
“…(57,1%) em relação à Anaplasma spp. (21,4%), divergindo dos achados de Ribeiro et al (13) , que analisaram 182 cães procedentes de Pato Branco ̶ PR e obtiveram 32,9% (60/182) de animais positivos para A. platys e todos negativos para E. canis, com base na Reação em Cadeia da Polimerase (PCR), assim como dos resultados obtidos por Witter et al (14) , que, utilizando a técnica de PCR associada à Reação de Imunofluorescência Indireta (RIFI), obtiveram 23,3% e 9,1% de animais reagentes para E. canis e A. platys, respectivamente, com base em análise realizada em 77 cães em Cuiabá − MT, além de 5,2% de coinfecção.…”
Section: Discussionunclassified
“…(57,1%) em relação à Anaplasma spp. (21,4%), divergindo dos achados de Ribeiro et al (13) , que analisaram 182 cães procedentes de Pato Branco ̶ PR e obtiveram 32,9% (60/182) de animais positivos para A. platys e todos negativos para E. canis, com base na Reação em Cadeia da Polimerase (PCR), assim como dos resultados obtidos por Witter et al (14) , que, utilizando a técnica de PCR associada à Reação de Imunofluorescência Indireta (RIFI), obtiveram 23,3% e 9,1% de animais reagentes para E. canis e A. platys, respectivamente, com base em análise realizada em 77 cães em Cuiabá − MT, além de 5,2% de coinfecção.…”
Section: Discussionunclassified
“…We reported a higher rate of infection compared to the rates of infection reported in other studies that were carried out in animals that had no clinical signs suggestive of infection by A. platys. RIBEIRO et al (2017) reported an infection rate of 32.9% in stray dogs in the state of Paraná. LASTA et al (2013) observed infection in 14.07% of stray dogs in the state of Rio Grande do Sul.…”
Section: Agent ------------------------------------Group-------------mentioning
confidence: 99%
“…The importance of these diseases has been highlighted by the small number of epidemiological studies that have already been carried out in the northern region of Brazil using molecular biology tools (RIBEIRO et al, 2017;SOARES et al, 2017;VIEIRA et al, 2018;PAULINO et al, 2018). Thus, the objective of our study was to determine the rates of incidence of these pathogens in domesticated and stray dogs in the municipality of Belém, Pará, Brazil.…”
Section: Parasitologymentioning
confidence: 99%
“…There are also reports of E. risticii infection [16]. However, to date in the Brazilian territory, the clinically important species for pets that cause hematological disorders in dogs are E. canis and A. platys [17,18]. E. canis has mononuclear cell tropism, mainly monocytes, whereas A. platys infects platelets [19].…”
Section: Etiology Occurrence and Distributionmentioning
confidence: 99%